Design & Development Micromouse For Robot Competition - Aw, Aaron Teik Hong (UTeM, 2008)
A micromouse is an autonomous robot which has to navigate through a maze. The aim is to reach the center of the maze as fast as possible. To achieve that, it will need several different components such as sensors, motors and a microcontroller. Sensors are used to obtain data of its surroundings. A microcontroller will then process that data and provide output to the motors. A chassis will accommodate all the components, and its size will be restrained only by the dimensions of the maze cell. Algorithms will have to be devised in order to successfully solve mazes.